2017
DOI: 10.1007/s11882-017-0681-6
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Macrophages in Allergic Asthma: the Forgotten Cell Awakes

Abstract: Purpose of Review The role of alveolar macrophages in innate immune responses has long been appreciated. Here, we review recent studies evaluating the participation of these cells in allergic inflammation. Recent Findings Immediately after allergen exposure, monocytes are rapidly recruited from the bloodstream and serve to promote acute inflammation. By contrast, resident alveolar macrophages play a predominantly suppressive role in an effort to restore homeostasis. As inflammation becomes established after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 83 publications
2
78
0
Order By: Relevance
“…In the meantime, the findings here suggest that lower‐SES youth may experience worse asthma outcomes partly because of increased monocyte trafficking to the airways and more aggressive clearance of antigens, both of which would presumably amplify downstream lymphocyte effector responses. Consistent with this scenario, there is increasing recognition that innate immune cells, including monocytes, play a role in both acute exacerbations of asthma, and the more chronic airway inflammation that characterizes poorly controlled disease …”
Section: Discussionmentioning
confidence: 93%
“…In the meantime, the findings here suggest that lower‐SES youth may experience worse asthma outcomes partly because of increased monocyte trafficking to the airways and more aggressive clearance of antigens, both of which would presumably amplify downstream lymphocyte effector responses. Consistent with this scenario, there is increasing recognition that innate immune cells, including monocytes, play a role in both acute exacerbations of asthma, and the more chronic airway inflammation that characterizes poorly controlled disease …”
Section: Discussionmentioning
confidence: 93%
“…Although there has been much debate about whether alternatively activated/M2 macrophages are proinflammatory, evidence is accumulating that under the appropriate circumstances, M2 macrophages can make an important contribution to driving inflammation, for example in host defence against viral or fungal infections [27,28]. Moreover, it is becoming increasingly clear that categorising macrophages into M1/M2 and further subdivisions is an oversimplification, in part because these cells exhibit marked phenotypic plasticity [29] and in part because newly recruited monocytes/ macrophages may have quite different functional characteristics to resident tissue macrophages [8]. Indeed, a comprehensive analysis of human macrophage activation in response to a diverse range of stimuli identified a spectrum of activation with at least 9 distinct activation patterns [30].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Macrophages are increasingly being recognised as important in the inflammation associated with allergic asthma [8]. In experimental allergen-induced acute exacerbations of asthmatic inflammation in mice, we have previously shown that macrophages secrete increased quantities of various pro-inflammatory cytokines, while at the same time exhibiting elevated expression of markers associated with alternative activation [9,10].…”
mentioning
confidence: 98%
“…Lung macrophages had long been overlooked as cellular participants in the development of allergic airway inflammation . However, recent studies in mouse models have revealed an important dichotomy in which resident AMs play largely suppressive roles, while recruited monocyte‐derived macrophages play largely pathogenic roles in allergic airway inflammation …”
Section: Introductionmentioning
confidence: 99%
“…4 However, recent studies in mouse models have revealed an important dichotomy in which resident AMs play largely suppressive roles, [5][6][7] while recruited monocyte-derived macrophages play largely pathogenic roles in allergic airway inflammation. 5,8,9 Given their paucity as well as their relative immobility in the normal mammalian lung, 10,11 AMs would be anticipated to employ paracrine means to restrain the inflammatory behavior of the alveolar and airway epithelial cells (ECs) which comprise this mucosal surface. A form of paracrine communication whose importance is increasingly appreciated involves the transfer of extracellular vesicles (EVs) containing various molecular species of cargo from donor to recipient cell.…”
Section: Introductionmentioning
confidence: 99%